Housing rent dynamics and rent regulation in St. Petersburg (1880–1917) - Konstantin A. Kholodilin; Leonid E. Limonov; Sofie R. Waltl (Explorations in Economic History, 2021)
This article studies housing rents in St. Petersburg from 1880 to 1917, covering an eventful period of Russian and world history. Digitizing over 5000 rental advertisements, we construct a state-of-the-art index – the first pre-war and pre-Soviet market data index for any Russian city. In 1915, a rent control and tenant protection policy was introduced in response to soaring prices following the outbreak of WWI. We document official compliance, rising tenure duration, and strongly increased affordability for workers. While the immediate prelude to the October Revolution was indeed characterized by economic turmoil, rent affordability did not dominate.
Keywords: C14; C43; N93; O18; 330; Rental market; Rent regulation; Intra-urban rent dynamics; Hedonic rent price index; Economic history; Pre-Soviet Russia; October Revolution